Water, health, and income: a review - Hoddinott, John F. (International Food Policy Research Institute, 1997)
This paper examines the impact of improved water access on health and incomes in the developing world, drawing on contributions from public health, economics, and anthropology. It argues that the biological pathways are reasonably well understood, with the effectiveness of interventions being ordered in the following way: improved household sanitation and hygiene practices; improvements in both quality and quantity of water supplies; increased quantity of water consumed and better water quality. However, the whole is greater than the sum of the parts; knowledge of hygienic practices plus improvements in sanitation plus use of greater quantities of water tend to lead to the largest improvements in health. By contrast, the economic" pathways are less well understood. The full economic returns to investing in improved water access have not been determined, nor is the distributional impact of water access known, either across or within households. Although it is possible to order these interventions in terms of effectiveness, this ranking omits any consideration of cost."